Hubungan Rasio Lingkar Pinggang Bagi Tinggi Badan (Lp/Tb) Terhadap Beratnya Penyakit Arteri Koroner - Vito Anggarino Damay; Fathy Fathini (Fakultas Kedokteran Universitas Pelita Harapan, 2018)
Adiposity assessment is a part of the evaluation in coronary artery disease (CAD) prevention. Waist to height ratio (WHtR) is one of adiposity parameter in CAD management guidelines. This cross sectional study enrolled 30 subject with stable CAD undergone elective coronary angiography. Eightyfive subjects has abnormal WHtR (≥0,5). Median WHtR is 0,54 with 0,471-0,706 range, and Duke CAD prognostic index with median 37 (range 19-82). Analysis using spearman’s rank correlation show a significant moderate positive correlation (r=0,425; p=0,019) between WHtR and Duke CAD prognostic index. Waist to height ratio could be one of valuable indicator for coronary artery stenosis severity. We conclude that there is a relationship between WHtR and Duke CAD prognostic index.